Influence of sport specialization on quality of life, physical literacy, and injury history in hockey players (International Journal of Athletic Therapy & Training, 2025)
Sport specialization and its effect on health-related quality of life, physical literacy, and injury among ice hockey players is poorly understood. We examined specialization patterns, quality of life, physical literacy, and injury history in a sample of 63 high school-aged hockey players. Thirty-eight percent of participants reported moderate specialization; over half of the sample reported high specialization. Highly specialized players spent a greater amount of weekly time per week in hockey activities (21.14 hr, 95% confidence interval [17.4, 24.88]) and reported a greater number of injuries when compared with moderate and low specializers (x2 = 0.026). Acute injuries were more prevalent than chronic or overuse injuries across all groups. No differences were observed on physical literacy or quality of life scores. Despite their increased participation and greater frequency of injuries, specialization did not significantly impact health-related quality of life.